1967
DOI: 10.1037/h0025250
|View full text |Cite
|
Sign up to set email alerts
|

Traditional sex attitudes and discrepant ability measures in college women.

Abstract: The hypothesis was investigated that girls avoid involvement in mathematics because of its masculine character. Girls grouped in the following ability score patterns were the dependent variables: 40 with low English and low mathematics, 48 with low English and average mathematics, 50 with average English and low mathematics, 50 with average English and average mathematics, 63 with average English and high mathematics, 50 with high English and average mathematics, and 50 with high English and high mathematics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1968
1968
1984
1984

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…However, generalizations from this study are hazardous because of small sample sizes. Elton and Rose (1967) found that girls who had higher mathematical than verbal scores on the American College Test (ACT) had more theoretical and less aesthetic (i.e., more masculine) interests as measured by the Omnibus Personality Inventory (OPI), and that girls with higher verbal than mathematical scores on the ACT had more cultural and artistic (i.e., more feminine) interests.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…However, generalizations from this study are hazardous because of small sample sizes. Elton and Rose (1967) found that girls who had higher mathematical than verbal scores on the American College Test (ACT) had more theoretical and less aesthetic (i.e., more masculine) interests as measured by the Omnibus Personality Inventory (OPI), and that girls with higher verbal than mathematical scores on the ACT had more cultural and artistic (i.e., more feminine) interests.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Thus, as in the Carlsmith (1964) study, masculine identification, or masculine role, was a predictor of large differences between verbal and mathematical scores on a college entrance examination. The findings of Elton and Rose (1967), however, are perhaps more easily accepted and interpreted than those of Carlsmith, because they do riot require that researchers reach back to an event in a person's early childhood as an explanation of the difference between his verbal and mathematical scores on a college admissions test. Many of the items on the OPI concern interests in reading, science, and other verbal-related and mathematics-related pursuits.…”
Section: Masculinity-femininity Of Interestsmentioning
confidence: 99%
“…The weights for the principal axis factor analysis of the OPI can be found in Elton and Rose ( 1967) . TABLE 1 presents the group means for actives and pledges for eight fraternities.…”
Section: Resultsmentioning
confidence: 99%